RAPD analysis of colchicine induced variation of the Dendrobium Serdang beauty - Khosravi, Alireza; Abdul Kadir, Mihdzar; Kadzemin, S. B.; Qamaruz Zaman, Faridah; De Silva, Angela Ee (Academic Journals, 2009)
Variation was detected in Dendrobium Serdang Beauty V (DSB V) plantlets regenerated from protocorm like bodies (plbs) induced by various concentration levels of colchicines in the Murashige and Skoog media (MS) supplemented with 1.5 mg/L IBA. RAPD analysis detected 6 - 26% variation in the regenerants from the mother plant. The highest variation was obtained in regenerates treated with 25 mg/L colchicine, which also exhibited reduced regeneration rates from plbs and mean plantlet fresh weight. RAPD analysis also showed high polymorphism between the mutated regenerant DSB V, and 13 species of the Dendrobiumgenera, and 13 orchids across generas. However, despite the 26% colchicine induced variation in the regenerants, all RAPD analysis revealed that DSB V was closely related to the mother plant. Thus, the RAPD technique is favourable for variation detection as it was sensitive enough to detect variations at species level and among somaclonal variants in this study.